Dari Kenosis ke Kepemimpinan Hamba: Filipi 2:6-8 sebagai Model Teologis Bagi Transformasi Gereja Masa Kini - Ariance Loru; Kalis Stevanus (Sekolah Tinggi Teologi Berita Hidup, 2025)
This study aims to analyze the concept of servant leadership based on Philippians 2:6-8 and its relevance to the modern church. The method used in this study is a qualitative approach through literature review and exegetical study. The focus of the study is directed at the practical theological realm of Jesus Christ's example of humility, self-emptying, and obedience to the point of death on the cross. The exegetical results indicate that servant leadership offers an alternative, transformative solution amidst the challenges of the modern church, such as secularization, technological development, religious pluralism, and socio-cultural change. The example of Jesus Christ, which teaches three main aspects of servant leadership: relinquishing personal rights, taking on the form of a servant, and living in obedience and sacrifice, will shape the character of Christian leaders who are humble, imbued with integrity, and contextual. This study confirms that servant leadership is not merely an organizational strategy, but a theological calling rooted in the example of Jesus Christ himself. Penelitian ini bertujuan untuk menganalisis konsep kepemimpinan hamba berdasarkan Filipi 2:6-8 serta relevansinya bagi gereja modern. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif melalui studi pustaka dan studi eksegesis. Fokus kajian diarahkan ke ranah teologis praktis terhadap teladan Yesus Kristus yang merendahkan hati, mengosongkan diri dan taat sampai mati di atas kayu salib. Hasil eksegesis menunjukkan bahwa kepemimpinan hamba memberikan alternatif yang solusi tranformatif di tengah tantangan gereja modern, seperti sekularisasi, perkembangan teknologi, pluralisme agama, serta perubahan sosial-budaya. Teladan Yesus Kristus yang mengajarkan tiga aspek utama kepemimpinan hamba, yaitu: melepaskan hak pribadi, mengambil rupa sebagai hamba, serta hidup dalam ketaatan dan pengorbanan akan membentuk karakter pemimpin Kristen yang rendah hati, berintegritas, dan kontekstual. Penelitian ini memberikan penegasan bahwa kepemimpinan hamba bukan sekedar strategi organisasi, melainkan panggilan teologis yang berakar pada teladan Yesus Kristus sendiri.